Impact of Digital Finance on Economic Growth: Nigerian’s Experience - Kehinde Adegoke Adeniji (Interdisciplinary Journal Of Lifelong Learning, 2025)
This study examines the impact of digital finance on economic growth in Nigeria, focusing on key payment channels such as Automated Teller Machine (ATM) transactions, Point of Sale (POS) systems, mobile money, web platforms, and cheque transactions. Using time-series data from 2012 to 2023, the analysis employs Ordinary Least Squares (OLS) regression to evaluate the relationship between these digital payment channels and Nigeria's Real Gross Domestic Product (RGDP). Results indicate a positive and significant influence of digital finance variables on economic growth, with POS transactions showing the strongest impact. The findings suggest that the adoption of digital financial systems enhances financial inclusion, reduces inefficiencies in banking operations, and fosters economic growth by integrating technology into financial transactions. This study underscores the need for policies that promote digital finance, lower transaction costs, and extend banking services to rural areas. Recommendations include improving digital infrastructure, encouraging usage through reduced charges, and developing financial instruments to support economic growth.